ANALISIS KEPUASAN DAN LOYALITAS KONSUMEN TERHADAP ATRIBUT TAHU TOP SUMEDANG (Suatu Kasus di Kedai Tahu Top Sumedang) - Nuraida Faradhilla; Meutia Meutia; Sri Mulyati (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2015)
Sumedang Tofu is one of the special food Sumedang city is starting cultivated in various citiesparticular region. This study aims to analyze the level of customer satisfaction and customer loyalty tothe attribute level the top Sumedang tofu. Attributes analyzed are taste, color, aroma, and texture. Thisstudy uses survey methods, site selection purposively selected with the consideration that the shop topSumedang tofu producer strategic places of business. The selection of respondents using accidentalsampling method by the number of respondents was 100 respondents. Acquisition of data derived fromprimary data and secondary data. Analysis tool is Importance Performance Analysis (IPA), CustomerPerformance Analysis (CSI) and pyramid loyalty. Importance Performance Analysis Based on theanalysis, attributes that should be maintained is the taste and texture, while the attributes in terms ofcolor and aroma should be further enhanced performance. Based on the analysis of CSI, store of toptofu Sumedang able to satisfy customers by 95.53%. The results showed that consumer loyaltypyramids that reach the highest levels is Satisfied Buyer with a percentage of 87%. The value of eachlevel of the Buyer Price by 58%, Liking the brand by 62%, 53% Habitual Buyer and Buyer Commitedby 28%. Overall respondents were satisfied and loyal with the attributes provided by the shop topSumedang tofu, it is evidenced by CSI and satisfied buyers value high.